Analisis Bangkitan Perjalanan Penduduk Pada Kompleks Perumahan Citra Sudiang Indah Makassar - Ricky Setiawan; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2022)
The existence of Citra Sudiang Indah housing in the Biringkanaya sub-district, PAI sub-district with a population of 17,177 people, as a land use will result in traffic generation. The trips generated by these residential families will increase along with the increase in income, increase in the number of family members, and choice of vehicle. The purpose of this research is (1) determine the characteristics of the population in the Citra Sudiang Indah housing estate. (2) find out the movement generation model in Citra Sudiang Indah housing estate. Using SPSS 28.0 . multiple linear regression method. Data collection using questionnaires and interviews (in-depth interviews) to collect research samples. This data collection was carried out to determine the characteristics of the population or household related to the number of motorcycle ownership, the number of private car ownership, the number of working families and the number of families attending school/college, the number of family members and the average household income. The results of the study indicate that motorcycle ownership, private car ownership, and the number of working families are variables that have a significant influence on population travel generation in the Citra Sudiang Indah housing estate. This can be seen in the multiple linear regression equation model, namely:Y = 0.585 + 0.311 X2 + 0.301 X3 + 0.411 X5